Evaluation of Interest Rate Policies in Creating Financial Stability and Price Stability in Indonesia - Algifari Algifari; Haryono Subiyakto; Astuti Purnamawati (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
This study aims to evaluate the interest rate policy (rediscount policy) by Bank Indonesia to create financial stability and price stability in Indonesia. This research used data on the SBI interest rate, exchange rate of rupiah to US dollar, inflation rate, and money supply in Indonesia from January 2014 to December 2021. The econometric model to test the research hypothesis is the structural equation model - partial least square. The results showed that the interest rate instrument to create financial stability in Indonesia was appropriate because the interest rate had a negative impact on the exchange rate. It means that if desired exchange rate will decrease (the rupiah appreciated) it can be done by increasing the interest rate. However, the policy of raising the interest rate can cause the inflation rate to rise. Because the interest rate has a positive effect on the inflation rate. The money supply can mediate the effect of the interest rate on the inflation rate in Indonesia.